The Complicated Origins of Cuban Masonry: The Temple of the Theological Virtues - Torres-Cuevas, Eduardo (2013)
How was Freemasonry introduced in the Spanish Empire’s Cuba? In those waters, constantly agitated by the struggle between the various imperialist forces during the transition between the eighteenth and nineteenth centuries, several different Freemasons and Freemasonries constantly traveled. This article offers an answer to this question, showing the dynamics of the complex origins of Freemasonry in Cuba.